Perilaku Self-Injury pada Remaja: Dampak Religiusitas dan Dukungan Sosial dalam Proses Coping - Shessa Alzuhra Putri Wibowo; Amanda Pasca Rini; Nindia Pratitis (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract This study aims to examine the relationship between religiosity and social support on self-injury behavior among adolescents. It involved 176 adolescents aged 12–24 years who have engaged in or are currently engaging in self-injury behaviors. Data were collected through questionnaires assessing levels of religiosity, social support, and self-injury behavior. Partial correlation tests revealed that religiosity and social support have a significant negative influence on self-injury behavior, with t-scores of -5.059 and -6.831, respectively (p < 0.05). This indicates that the lower the level of religiosity and social support received by adolescents, the higher their tendency to engage in self-injury. Multiple regression analysis revealed an R-square value of 0.445, indicating that religiosity and social support collectively explain 44.5% of the variation in self-injury behavior. The F-test yielded a value of F = 4.749 with a significance of 0.010 (p < 0.05), confirming that these two variables are predictors of self-injury behavior. Additionally, the study found that religiosity contributes 18.26% and social support contributes 24.70% to the variation in self-injury behavior, with a total contribution of 42.96% (R Square). These findings highlight the significant role of both variables in influencing self-injury behavior. Keywords: Self-Injury, Religiosity, Social Support, Adolecents, Correlations Abstrak Penelitian ini bertujuan untuk mengkaji hubungan antara religiositas dan dukungan sosial terhadap perilaku melukai diri pada remaja. Penelitian ini melibatkan 176 remaja berusia 12–24 tahun yang telah atau sedang melakukan perilaku melukai diri. Data dikumpulkan melalui kuesioner yang menilai tingkat religiositas, dukungan sosial, dan perilaku melukai diri. Uji korelasi parsial menunjukkan bahwa religiositas dan dukungan sosial memiliki pengaruh negatif yang signifikan terhadap perilaku melukai diri, dengan t-score masing-masing -5.059 dan -6.831 (p < 0.05). Ini menunjukkan bahwa semakin rendah tingkat religiositas dan dukungan sosial yang diterima oleh remaja, semakin tinggi kecenderungan mereka untuk melakukan perilaku melukai diri. Analisis regresi berganda menunjukkan nilai R-square sebesar 0.445, yang berarti religiositas dan dukungan sosial secara kolektif menjelaskan 44.5% variasi dalam perilaku melukai diri. Uji F menghasilkan nilai F = 4.749 dengan signifikansi 0.010 (p < 0.05), mengonfirmasi bahwa kedua variabel ini adalah prediktor perilaku melukai diri. Selain itu, penelitian menemukan bahwa religiositas menyumbang 18.26% dan dukungan sosial menyumbang 24.70% terhadap variasi perilaku melukai diri, dengan total kontribusi sebesar 42.96% (R Square). Temuan ini menyoroti peran signifikan kedua variabel dalam mempengaruhi perilaku self-injury.